The Role of Green Organizational Culture and Green Work Engagement Mediation in the Influence of Green Human Resource Management on Environmental Performance in Private Universities in Batam City - Muchsinati, Evi Silvana; Sari, Wanda Pramitha; Farid, Ridhayati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Industrial and educational growth in Batam City has increased energy consumption, carbon emissions, and waste, including at private universities (PTS) that have not yet fully implemented environmentally friendly practices. The gap between green policies and campus environmental performance still exists due to the low contribution of human resources in supporting sustainability, particularly through green organizational culture (GOC) and green work engagement (GWE). This study aims to analyze the influence of green human resource management (GHRM) on environmental performance (EP) at PTS in Batam and to examine the mediating role of GOC and GWE. A total of 260 respondents from UIB, UPB, and UIS were involved through an online questionnaire in December 2024–March 2025, with 26 measurement items on the variables of GHRM, GWE, GOC, and EP using a five-point Likert scale. The analysis was conducted using PLS-SEM through SmartPLS 4.0. The results showed that all indicators were valid and reliable, with outer loading values above 0.7, AVE exceeding 0.5, and reliability above 0.9. The main findings show that GHRM has a positive effect on GWE, GOC, and EP, while GWE and GOC also have a significant effect on EP. This confirms that green work culture and engagement are important mechanisms that bridge the implementation of GHRM in improving campus environmental performance. Overall, this study shows that effective GHRM integration can strengthen environmentally oriented organizational behavior and culture, thereby promoting improved environmental performance at private universities in Batam City.